2016
DOI: 10.1109/access.2016.2587581
|View full text |Cite
|
Sign up to set email alerts
|

A New Wavelet Denoising Method for Selecting Decomposition Levels and Noise Thresholds

Abstract: A new method is presented to denoise 1-D experimental signals using wavelet transforms. Although the state-of- the-art wavelet denoising methods perform better than other denoising methods, they are not very effective for experimental signals. Unlike images and other signals, experimental signals in chemical and biophysical applications for example, are less tolerant to signal distortion and under-denoising caused by the standard wavelet denoising methods. The new method 1) provides a method to select the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
153
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 207 publications
(155 citation statements)
references
References 47 publications
2
153
0
Order By: Relevance
“…This study is used wavelet transform because of simple and naive for denoise represented of single level discrete 1-D wavelet transform that is the state-of-the-art wavelet denoising [9]. This method has become common signal processing technique in different area and the result indicate that wavelet functions Daubechies 44 (db44) provides a better fit to tested biosignals [22] but experiment of this study is found that the Coiflets1 wavelet is better suited in this study.…”
Section: The Wavelet Shrinkage Denoising Methodsmentioning
confidence: 73%
See 4 more Smart Citations
“…This study is used wavelet transform because of simple and naive for denoise represented of single level discrete 1-D wavelet transform that is the state-of-the-art wavelet denoising [9]. This method has become common signal processing technique in different area and the result indicate that wavelet functions Daubechies 44 (db44) provides a better fit to tested biosignals [22] but experiment of this study is found that the Coiflets1 wavelet is better suited in this study.…”
Section: The Wavelet Shrinkage Denoising Methodsmentioning
confidence: 73%
“…The solutions of it are a detail wavelet coefficient is either a signal or a noise coefficient that the hard thresholding is better suited, whereas it is both signal and noise that the soft thresholding is better suited and the wavelet shrinkage method better signal denoising with minimum computation complexity [9] and wavelet shrinkage denoising algorithm (see Table 1 and Fig. 1) where S(x) is a noisy speech of input signal, Di is a Detail wavelet coefficient of noisy speech where i = 1, 2, …, n, Ai approximate coefficient is where i = 1, 2, …, n, and the S(x') is noisy speech of output signal.…”
Section: The Wavelet Shrinkage Denoising Methodsmentioning
confidence: 99%
See 3 more Smart Citations